Measuring social capital in the context of disasters - Aldrich, Daniel (Henry Stewart Talks, 2022)
Bonding, bridging and linking ties, Hurricane Katrina, Tsunami in Tohoku, Japan, Survival, recovery and K6 scores, Ibasho experiment